Analisis Pengaruh Parameter Kompaksi Terhadap Nilai CBR Berdasarkan Standar dan Kriteria Jalan Tambang PT Bukit Asam Tbk. Tanjung Enim - Mitha Elisza; Mardiah Mardiah; Haslen Oktarianty (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2019)
This study analyzes the effect of compacting parameters on CBR values based on PT Bukit Asam Tbk's standards and criteria. The problem behind this research is that the overburden target at the TAL-West mining site to the South sump disposal is not affected by the speed of the transport equipment which is caused by the damaged road because the carrying capacity does not reach the standard so the circulation time increases. Therefore it is necessary to analyze the effect of compacting on CBR values based on company standards and criteria to meet the production target in April 2019 of 1,500,000 BCM, while the realization only reaches 1,379,160 BCM. The research method used is a linear regression method that analyzes the influence and relationship of independent variables such as material physical properties, compacting parameters and dependent variables, namely CBR values. The results of this study are that the physical properties of material have a relationship and influence on CBR values. Compaction parameters have a relationship with CBR values such as small dry volume weight so CBR value increases while optimum water content is large, CBR value decreases. Based on the evaluation of company standards and criteria, the best material in the B2C-22 sample with water content of 9.49%, density of 2.77, CBR value of 74.87% of the type of inorganic clay with light ash.